The meaning of illicit drug usage in patients of a public prevention program - Crives, Miranice Nunes dos Santos; Dimenstein, Magda (Saúde e Sociedade, 2003)
The purpose of the study was to identify the meaning of drug consumption in patients of the Alcohol and Drug Prevention and Treatment Program at the Pirangi Health Center in Natal, RN. Fourteen interviews were conducted with drug users who were under, or had been released from treatment, and that were in the program voluntarily or by court order. Discourse analysis of the data showed that alcohol and marijuana were the most common drugs used and that the major motivating factors were: a) to escape from problems; b) curiosity; c) the influence of friends; d) dissatisfaction with life; e) pleasure, and f) personal weakness, confirming the multi-determinism and the complexity of the problem. The use of drugs to these clients had both a negative meaning associated with physical and social consequences, and a positive one related to a feeling of well-being and of "forgetting " problems. These socially constructed representations originate in a context where the user of drugs is seen as a "marginal" or a "delinquent" person, thereby imposing a punitive and discriminatory perspective on the problem.